1973
DOI: 10.1176/ajp.130.9.1018
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Induced Folliculitis

Abstract: diabeteh insipidus: in vivo and in vitro studies. J Clin Invest sensitive adenyl cyclase. Life ki [I] 9:765 770. 1970 51:IOXI 1091. 1972 18. Demers RG. Heninger GR: Sodium intake and lithium treatment 16. Harris CA. Jenner FA: The inhibition of the action of vasopressin in mania. Am J Psychiatry 128: 100 104. 197 1 by lithium ions (abstract). J Physiol (London) 200:59. 1969 19. Thomson T, Schou M: Renal lithium excretion in man. Am J Phys-17. Dousa T. Hcrchter 0: The erect of NaCl and LiCl on vasopressiniol 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Calloway 29 reported pruritic maculopapular eruptions and pre‐tibial ulcerations in some patients receiving lithium. Others have shown lithium related folliculitis, 30 ac‐neform eruptions, 31,32 seborrheic dermatitis, and palmoplantar hyperkeratosis 33…”
Section: Discussionmentioning
confidence: 99%
“…Calloway 29 reported pruritic maculopapular eruptions and pre‐tibial ulcerations in some patients receiving lithium. Others have shown lithium related folliculitis, 30 ac‐neform eruptions, 31,32 seborrheic dermatitis, and palmoplantar hyperkeratosis 33…”
Section: Discussionmentioning
confidence: 99%
“…Appearance or exacerbation of acne in patients -especially women [2,3,6] treated with lithium may be related to the lithium therapy [2,3,6] without signs of general lithium intoxication, and in spite of therapeutical serum lithium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In 1973, Rifkin et al [3] described 18 patients, 10 of whom were women, who had got lithium folliculitis located on the arms and legs. Yoder [6] observed 4 female patients who had acneiform eruption on the face, neck and all noted an exacerbation of their acne after lithium carbonate therapy.…”
mentioning
confidence: 99%
“…Folliculitis is frequently associated with lithium therapy 7 . It may be asymptomatic or may present with transient itching secondary to lithium excretion in the sweat, producing local irritation of the hair follicles 97,98 . It occurs in the initial period of treatment or may take several months to develop.…”
Section: Dermatologic Manifestationsmentioning
confidence: 99%
“…60 In vitro studies of cultures of normal human skin with lithium have demonstrated the direct role of lithium in epidermal hyperproliferation, leading to the modification of epidermal barrier function by the production of intercellular edema and vacuolar alteration with the formation of small cavities in the upper dermis. 61 Patients with a positive family history for psoriasis should be carefully evaluated for the potential Table 1 Classification of dermatologic manifestations of lithium therapy Inflammatory disorders [36][37][38][39][40][41][42]95,[127][128][129][130]144,146,148,156 Psoriasis and pustular psoriasiform eruption, erythema multiforme, exfoliative dermatitis, fixed drug eruption, maculopapular eruption, eczematous reaction, seborrheic dermatitis Disorders of sebaceous/apocrine glands 21,25,[99][100][101] Acne and acneiform eruption, hidradenitis suppurativa Disorders of the hair and nails 46,68,[77][78][79]92,93,97,98 Alopecia, folliculitis, onychomadesis, nail dystrophy, nail discoloration Mucosal lesions [102][103][104][105]107,109,143 Geographic tongue, lichenoid stomatitis, oral mucosal ulcerations, vaginal ulcerations Keratinization disorders…”
Section: Psoriasismentioning
confidence: 99%